THE BALINESE COOKING AND LANGUAGE CLASS AS A TOURISM ATTRACTION OF SPECIAL INTEREST - Francisca Titing Koerniawaty (Jurnal Ilmiah Hospitality Management, 2016)
The study aim is to design and develop the Balinese cooking and language class as a tourism attraction of special interest in Bedulu, Gianyar Bali to create an atmosphere that is really close to Balinese culture, in turn will create a travel experience which is more experimental and memorable for the visitors. All Balinese ingredients will be introduced in Balinese language. The urgency of this study are as follows: (1) there is potential in Bedulu village as a tourism attraction that is unique and leads to special interest destination through some of the cultural heritage and beauty of nature, (2) the cooking class that has been presented needs to be developed further so that the visitors can obtained a travel experience which is more experimental and memorable through the participation of local community, (3) the geographical location of Bedulu village which can be positioned as the area of special interest tourism destination of educational and cultural.Â  This research method is Design and Development Research. This study is to design and develop sistematically from the process of designing and developing the Balinese cooking by introducing several Balinese terminologies in cooking. The Balinese cooking class should be designed and developed by considering the hygiene and sanitation standards, health and benefit.